2011
DOI: 10.2202/1548-923x.2251
|View full text |Cite
|
Sign up to set email alerts
|

Developing Palliative Care Competencies for the Education of Entry Level Baccalaureate Prepared Canadian Nurses

Abstract: Educational preparation of health professionals for Palliative and End of Life Care (PEOLC) is inadequate, and nurses are no exception. In 2004, the Canadian Association of Schools of Nursing struck a Task Force to develop PEOLC competencies to address this issue. The development of national PEOLC nursing competencies involved a multi-step, emergent, interactive, and iterative process. An overarching principle guiding this process was building national consensus about the essential PEOLC specific competencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…For example, in the development of competency frameworks, only five papers in this review published before 2010 included service users ( 13 , 22 , 38 , 43 ). Engagement with patient and family advocacy groups broadens the conceptualisation of competency, particularly given the recent increase in consumer participation in health care ( 4 , 65 ). Service user participation in health care research may provide unique information about the effectiveness of health care systems including how to improve patient experience and outcomes ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the development of competency frameworks, only five papers in this review published before 2010 included service users ( 13 , 22 , 38 , 43 ). Engagement with patient and family advocacy groups broadens the conceptualisation of competency, particularly given the recent increase in consumer participation in health care ( 4 , 65 ). Service user participation in health care research may provide unique information about the effectiveness of health care systems including how to improve patient experience and outcomes ( 95 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the three mixed-method papers utilised a longitudinal quantitative approach and thematic analysis to analyse qualitative data in response to open ended questions [ 36 ]. The second utilised a consultation survey via telephone and email, and a consensus-based comment and national approval process for data analysis [ 40 ]. The third paper used a 12-question survey that utilised mixed-method approach to evaluate students [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Canadian teacher training needs were recently illustrated as a concern through Brajtman, Fothergill-Bourbonnaia, Fiset, and Alain's 2009 single-site study which found only modest knowledge levels about the care of dying persons among 53 nurse educators [ 30 ]. Recently, the Canadian Hospice Palliative Care Association along with a number of Canadian nursing groups and Health Canada have collectively initiated a process to increase the amount of death education in nursing programs and also ensure its certainty there [ 31 ].…”
Section: Resultsmentioning
confidence: 99%